2009
DOI: 10.1111/j.1365-2230.2009.03571.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia–ischaemia is involved in the pathogenesis of vulvar lichen sclerosus

Abstract: HI is involved in the pathogenesis of vulvar LS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Hypoxia, ischemia, and vascular damage are due to increased GLUT1 and decreased vascular endothelial growth factor (GF) expression in affected skin. [5] The effect of cell-mediated cytotoxicity has also been defined. [6] Although many authors have described LS and scleroderma as closely related entities or even their associations have been seen, there is no systemic involvement in LSA.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Hypoxia, ischemia, and vascular damage are due to increased GLUT1 and decreased vascular endothelial growth factor (GF) expression in affected skin. [5] The effect of cell-mediated cytotoxicity has also been defined. [6] Although many authors have described LS and scleroderma as closely related entities or even their associations have been seen, there is no systemic involvement in LSA.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Sander et al demonstrated that lesional skin showed lipid peroxidation of epidermal basal cell layers, oxidative DNA damage, and oxidative protein damage. The finding of high glut‐1 and low vascular endothelial growth factor (VEGF) expression in affected skin supports the theory that hypoxia and ischemia play a role in LS . Local factors such as trauma, sunburn, and radiation may also contribute.…”
Section: Discussionmentioning
confidence: 59%
“…Regarding the cutaneous vascular structures, there is damage of the vascular endothelium and capillaries, and disruptions of the capillary morphology. Hypoxia markers were suggestive of hypoxia involvement in the VLS pathogenesis (39) .…”
Section: Gineco Eumentioning
confidence: 97%